A path of university academic affiliation. Students who do research into their own training (Praxis Educativa, 2022)
We present an analytical reflection on our experience as adscriptas a la investigación, a term used in Spanish to describe the role of those who volunteer as students to be in an apprenticeship relationship with experienced professors-researchers at our public university (School of Humanities) in the metropolitan area sorrounding the city of Buenos Aires. We have analyzed and written our piece in two voices, as we are both apprentices. Methodologically, we start from our work logs, audio recordings and photographs to make an analytical description of the assignment, which is divided into three sections: the place of others in the construction of knowledge, word in dispersion and resistance, and spaces and bodies that communicate in themselves. Our reflection accounts for the learning and transformation opportunities generated from the implementation of a new pedagogical practice for us. Thus, we observe that a space was created in connection with others that favored parity, horizontal communication, and, together with it, the collective construction of new knowledge based on local epistemologies.
Keywords: learning; experience; research; democracy; adscripción